Role of ploidy in colonization of alpine habitats in natural populations of Arabidopsis arenosa - Wos, Guillaume; Mořkovská, Jana; Bohutínská, Magdalena; Šrámková, Gabriela; Knotek, Adam; Lučanová, Magdalena; Španiel, Stanislav; Marhold, Karol; Kolář, Filip (Annals of botany, 2019)
BACKGROUND AND AIMS: Polyploidy is an important driver of plant diversification and adaptation to novel environments. As a consequence of genome doubling, polyploids often exhibit greater colonizing ability or occupy a wider ecological niche than diploids. Although elevation has been traditionally considered as a key driver structuring ploidy variation, we do not know if environmental and phenotypic differentiation among ploidy cytotypes varies along an elevational gradient. Here, we tested for the consequences of genome duplication on genetic diversity, phenotypic variation and habitat preferences on closely related diploid and tetraploid populations that coexist along approx. 2300 m of varying elevation. METHODS: We sampled and phenotyped 45 natural diploid and tetraploid populations of Arabidopsis arenosa in one mountain range in Central Europe (Western Carpathians) and recorded abiotic and biotic variables at each collection site. We inferred genetic variation, population structure and demographic history in a sub-set of 29 populations genotyped for approx. 36 000 single nucleotide polymorphisms. KEY RESULTS: We found minor effects of polyploidy on colonization of alpine stands and low genetic differentiation between the two cytotypes, mirroring recent divergence of the polyploids from the local diploid lineage and repeated reticulation events among the cytotypes. This pattern was corroborated by the absence of ecological niche differentiation between the two cytotypes and overall phenotypic similarity at a given elevation. CONCLUSIONS: The case of A. arenosa contrasts with previous studies that frequently showed clear niche differentiation between cytotypes. Our work stresses the importance of considering genetic structure and past demographic processes when interpreting the patterns of ploidy distributions, especially in species that underwent recent polyploidization events.
Keywords: genetic variation; polyploidy; Arabidopsis arenosa; Arabidopsis; Ploidies; multivariate statistics; Humans; ploidie; niche differentiation; polyploidie; lidé; Polyploidy; Alpine adaptation; Europe; RAD-sequencing; Evropa; ekosystém; Ecosystem